Satire in the service of history. On the phenomenon of Tabarnia in Catalonia - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2020)
The paper analyzes the phenomenon of Tabarnia, a grassroots social movement aiming to expose and counter the absurdities of the Catalan independence nationalism. The adherents of Tabarnia employ irony, situational humour, performance and historical re-enactment to ridicule and neutralize the nationalist discourse.